Implementing Project-Based Learning with Loose Parts in Early Childhood Education: A Qualitative Descriptive Study - Nur Aisyah, Eny; Utamimah, Sri; Baharun, Hasan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
This study explores the implementation of Project-Based Learning (PjBL) using loose-part media in early childhood education at RA Umi Sundari, a private ECE institution in Indonesia. PjBL is recognized for promoting active, meaningful learning by engaging children in real-world projects that integrate exploration, problem-solving, and collaboration. Despite its growing adoption, the integration of PjBL with loose-part media—flexible, open-ended materials such as stones, bottle caps, or sticks—remains under-researched, especially in the context of private early childhood settings. Employing a qualitative descriptive method and an intrinsic case study design, this research investigates how PjBL with loose parts supports the cognitive, motor, and social development of young children. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using thematic analysis. Findings reveal that loose-part-based PjBL fosters creativity, independence, and critical thinking while enhancing children’s enthusiasm for learning. Teachers played a crucial role as facilitators, guiding exploration through open-ended questions, emotional support, and structured reflection. The study also identifies several challenges, including uneven teacher preparedness, limited material availability, and time constraints for project planning. While the learning outcomes were positive, the research was limited to a single institution and a short timeframe. Therefore, future studies should explore broader applications, long-term impacts, and potential integration with digital tools. This study contributes to the growing body of knowledge on early childhood pedagogical innovation by offering a contextually relevant model for enhancing child development through PjBL and loose-part integration.